IDENTIFIKASI KOMPETENSI CUSTOMER SERVICE PADA BANK PERKREDITAN RAKYAT DENGAN METODE JOB COMPETENCY ASSESMENT (JCA) - Marlinda Dini Hapsari; Jeni Wulandari; Fenny Saptiani (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2022)
This study aimed to identify customer service competencies using the Job Competency Assessment (JCA) Method. This type of research uses a qualitative approach. Qualitative research obtains research subjects from informants using purposive sampling technique, namely the amount of information as much as 9 people according to selected criteria that are relevant to the research problem. Data analysis in this study was obtained from interviews, observation and documentation. At the interview stage the researcher used the Job Competency Assessment (JCA) Method to assess the competencies possessed by individuals. Based on the results obtained, it shows that there are 10 CS competencies in Bank Eka namely attention to clarity of tasks (attention to order), customer orientation (customer service orientation), enthusiasm for achievement (achievement orientation), self-control (self-control), impact and influence (impact and influence), empathy (interpersonal understanding), self-confidence (self-confidence), ability to direct (direction), special skills (personal expertise), cooperation (teamwork), 4 out of 10 competencies appears. The most concerned are clarity of tasks (attention to order), customer oriented (customer service oriented), passion for achievement (achievement orientation), self-control. This competency can later be more challenging, maintained and improved. ABSTRAK Penelitian ini bertujuan untuk mengidentifikasi kompetensi customer service dengan menggunakan Metode Job Competency Assesment (JCA). Jenis penelitian ini menggunakan pendekatan kualitatif, dengan jumlah informan sebanyak 9 orang yang ditentukan secara purposive. Teknik pengumpulan data menggunakan Behavioral Event Interview (BEI), observasi dan dokumentasi. Berdasarkan hasil penelitian, terdapat 10 kompetensi pada CS di BPR, dengan kompetensi prioritas pada kompetensi perhatian terhadap kejelasan tugas (concern for order), beriorientasi kepada pelanggan (customer service orientation), semangat untuk berprestasi (achievement orientation), pengendalian diri (self-control). Sementara kompetensi pendukung lain yakni kompetensi dampak dan pengaruh (impact and influence), empati (interpersonal understanding), percaya diri (self-confidence), kemampuan mengarahkan (directiveness), keahlian khusus (personal expertise), dan kerjasama (teamwork),